Reimagining Learner-Centred Education in the Age of Artificial Intelligence: A Critical Review of Child Development, Inclusive Pedagogy, Curriculum Reform, Assessment Practices, and Employability under NEP 2020 - Dr. Poonam Khurana, Dr. B. Chitradevi, Dr. T. Suresh, Dr. Zeba Siddiqui, S.Palpandi, Dr. Sachin Sahebrao Zende, Mushini Srikanthakumari (Journal of Daoist Studies, 2026)
The rapid expansion of artificial intelligence in education has reopened a fundamental question: whether educational systems are designed around the learner or around institutional routines of teaching, testing, and certification. In India, the National Education Policy 2020 provides a major policy opportunity to move from content-heavy, examination-oriented education toward holistic, competency-based, inclusive, multidisciplinary, and skill-linked learning. However, policy transformation cannot be reduced to digitalization or the adoption of AI tools. A genuinely learner-centred education system must be grounded in child growth and development, cognitive diversity, social-emotional learning, inclusive pedagogy, curriculum flexibility, ethical assessment, multilingual education, and employability-oriented learning pathways. This review critically examines the intersection of AI-enabled teaching and learning, NEP 2020 reforms, inclusive education, assessment transformation, and future employability. It argues that AI can strengthen learner-centred education only when it is embedded within sound pedagogical philosophy, teacher agency, equity safeguards, data privacy, and contextual sensitivity. The paper synthesizes evidence from educational policy, child development research, inclusive education frameworks, global AI guidance, and comparative education systems. It proposes a multidimensional framework in which AI functions not as a replacement for teachers, but as an adaptive support system for diagnosis, personalization, feedback, accessibility, curriculum enrichment, and employability mapping. The review concludes that India’s educational transformation will depend not merely on introducing AI tools, but on designing humane, equitable, developmentally appropriate, and future-ready learning ecosystems aligned with the deeper spirit of NEP 2020.